Model of Quality Management System Using Malcolm Baldrige Criteria in Nursing Education in Surabaya - A. Aziz Alimul Hidayat; Stefanus Supriyanto; Nursalam Nursalam (Universitas Airlangga, 2015)
Introduction: Most of the quality of Nursing Education in Surabaya is still at the low level. It is due to the fact that the process and job performances which have not been integrated yet, systematic and fl exible which are in line with the capacity of the organization and the needs of graduates. This study aims to develop a model of quality management systems of Nursing bachelor’s degree program based on the Malcolm Baldrige Criteria For Performance Excellence.Methods: The method used is a cross sectional survey design. This research was conducted with a sample of eight institutions and twenty four of respondents. The data was collected by means of interviews, questionnaires and documentation. Analysis of the data used Partial Least Square (PLS).Results: The results showed that 1) leadership affects the study program as well as the profi le that affects job performances; 2) Leadership affects the strategic planning as well as the strategic planning that affects focus of Human Resources. In addition, the focus of human resources affects the focus process and fi nally affects job performances as well; 3) customer focus affects leadership as well as leadership affects strategic planning. As the impact, strategic planning affects focus of human resources and it affects similarly on the focus process and fi nally affects job performances; 4) All variables are affected by measurements, analysis and knowledge management, except in strategic planning.Conclusion: Based on the above results, the model of quality management system can be developed by using the Malcolm Baldrige criteria for the purpose of increasing the quality of Nursing Study Program. On the other hands, this model can be used as a reference of the organization at the level of Nursing Study Program (Strategic Business Unit) to restructure the performance of the college in global competition.